Breeders’ and Farmers’ Exceptions: How Valuable Are They for the World and Are They a Necessity for the BRICS Countries? - O. Gavrilova (BRICS Law Journal, 2020)
These days, the world and every country in it are faced with the task of ensuring food security for people. It’s of current interest also for the BRICS countries. The ability to access genetic information and materials for seed production depends on intellectual property regimes. A lack of access to them is a main barrier for contribution in the development of plant varieties. This situation leads to dependence on obtaining hybrid varieties from foreign companies, which poses a threat to food security. It seems that to ensure freedom of research priorities there is a need to provide an opportunity to commercialize new breeding achievements resulting from such discoveries. Correct policymaking also includes the issue of regulating the situation when a patent and a certificate of ownership of the new plant variety are issued to different persons or companies. Capturing in legislation the breeders’ exception is necessary for the use of the patented invention in the frame of creating, discovering and developing a new plant variety. The biodiversity of seeds is a high stakes matter especially for the developing countries, where there are many challenges for smallholder farmers. The guarantee of the farmers’ right to use the saved seeds on their own farms and to exchange such seeds between themselves may be one of the aspects of food security as it is a base of the traditional agriculture economy in some countries, where smallholder farmers play a significant agricultural role. Also the position and scope of farmers’ rights and privileges, based on legislation and, especially, on judicial cases, shows a side of independence on international corporations in the agricultural sector.